The Law of Employee Benefit Plans - David Ziskind (Washington University Law Quarterly, 1955)
What are commonly called “fringe benefits” in union agreements are formed out of threads taken from many parts of the fabric of law: a large skein of contract law; binding threads from the law of trusts, agency and taxation; and many colorful strands from a host of labor law statutes. The legal principles are for the most part not unique or novel. Rather, the accumulation of new economic and social arrangements has brought together a variety of familiar legal rules that take on the appearance of a system or body of interrelated legal doctrines. In light of the current Congressional investigations, there may soon be special legislation for employee benefit plans. Such legislation will be woven from threads of the present law on the subject; hence, this paper will undertake to trace the salient filaments of that law.
Keywords: Insurance; Labor law